Démographie et urbanisation au Sahara algérien à l’aube du XXIe siècle - Yaël Kouzmine; Jacques Fontaine (Les Cahiers d’EMAM)
Since the 1950’s, the population of the Algerian Sahara continued to grow faster than the northern one. Therefore today, more than one Algerian in ten lives in the Sahara, against one in fifteen in the early 1960s. This population is increasingly urban and important cities are not rarer in the Sahara. This evolution is mainly due to a natural demographic increase which still remains high and to the developmental and controlling policies of the territory leads by the Algerian state. But this general trend is not uniform on the whole saharan regions and between the periods. This paper aims to analyse the demographic growth and structures of the Saharan population, in link with and the urbanization movement which deeply affected the Algerian Sahara since 1950.